RAB27B inhibits proliferation and promotes apoptosis of leukemic cells via 3-Hydroxy butyrate dehydrogenase 2 (BDH2). Issue 3 (1st March 2022) - Meng, Can; Huang, Li; Fu, Xiangjun; Wu, Bin; Lin, Lie
ABSTRACT: RAB27B is a member of Ras-like small GTPases that plays a role in endocytosis, exocytosis, and vesicle trafficking. We made an attempt to study the impacts of RAB27B on the proliferation and apoptosis of acute myeloid leukemia (AML) cells. The silencing of RAB27B was induced by siRNA for the detection of proliferation, cell cycle, and apoptosis, respectively by Cell Counting Kit-8 (CCK8), flow cytometry, and TUNEL. Related markers were also evaluated by Western blot analysis. The interaction between RAB27B and BDH2 was predicted by bioinformatics analysis and determined by immunoprecipitation. The gain of function of BDH2 was also detected by these functional assays. RAB27B exhibited high levels in AML cells, and RAB27B silencing led to reduced proliferation, increased cell cycle arrest and apoptosis levels. Then, the interaction between RAB27B and BDH2 was confirmed. Moreover, the effects of RAB27B inhibition on the proliferation, cell cycle arrest, and cell apoptosis were abolished after BDH2 overexpression. RAB27B inhibits proliferation and promotes apoptosis of leukemic cells by interacting with BDH2. Targeting RAB27B might be an effective method for the treatment of AML. Graphical Abstract: uf0001